The impact of smoking on meniscus surgery: a systematic review - Jan Zabrzyński; Jakub Pękala; Maria Zabrzyńska; Przemysław Pękala; Łukasz Łapaj; Robert F LaPrade (EFORT Open Reviews)
Purpose: To provide a comprehensive, systematic review on the relationship and effects of smoking on clinical outcomes after meniscus surgery. Methods: The following combination of keywords was entered into the electronic search engines: meniscus, meniscus repairs, meniscectomy, meniscal tear, meniscus excision AND (smoke OR smoking OR nicotine OR tobacco). The year of the study, country, type of study, number of subjects, medial/lateral/both menisci, body mass index, smoking status, mean age, gender, follow-up, type/pattern of injury, surgical implications and clinical outcomes were recorded. Results: A total of 23 studies published in 2013–2024 were included in the analysis. In ten studies, the meniscus injury was associated with an anterior cruciate ligament (ACL) tear. In four studies, the effect of smoking on meniscal allograft transplantation (MAT) was investigated. The neutral effect of smoking on meniscus surgery was revealed in nine studies, and only one of them focused on isolated meniscus pathology and surgery. The negative effect of smoking on meniscus surgery was shown in ten papers, with four papers focused on isolated meniscus tears and six papers presenting data with concurrent ACL reconstructions. Conclusions: This systematic review found that the results regarding the impact of smoking on meniscus repair outcomes were conflicting. Nevertheless, MAT and meniscus repair performed in the presence of concurrent ligamentous injury, both being demanding surgical procedures, require reduction of factors that may contribute to failure. Therefore, cessation of smoking in patients undergoing these procedures is highly advised.